Sustainable Accounting and Environmental, Social, and Governance (ESG) Reporting: Challenges and Implementation in Indonesian Companies - Setiatin, Tuti (GoAcademica Research & Publishing, 2025)
The implementation of sustainable accounting and ESG reporting in Indonesia has become a strategic issue that continues to grow in line with the increasing demand for transparency from both global and domestic stakeholders. However, its implementation still faces various obstacles, both within the company and due to complex external factors. The imbalance in readiness between sectors, limited infrastructure, and minimal data integration are real challenges in realizing comprehensive ESG reporting. This study aims to identify obstacles and accelerate the implementation of ESG in corporate accounting practices in Indonesia. The study was conducted using a qualitative approach and data collection through literature reviews, previous studies, and relevant documents. The data obtained were described descriptively and qualitatively to explore patterns, dynamics, and strategies that can be accepted by the company. The results of the study show that the role of leadership, desire literacy, regulatory support, and multi-party collaboration greatly determine the success of ESG reporting. The implementation of the acceleration strategy requires a comprehensive internal transformation and the use of digital technology. Public policy support and government incentives are key to creating an effective and sustainable ESG reporting ecosystem in Indonesia.